2018
DOI: 10.4067/s0718-221x2018005003101
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization, hardness and termite resistance of Quercus cerris heartwood from Kosovo

Abstract: Quercus cerris, the Turkey oak, is an oak species native to southern central and southeastern Europe, extending into southwestern Asia. It is present in a large extent in the forests of the Republic of Kosovo, and at present used mainly for bio-energy. The potential use of Quercus cerris wood for construction and higher value wood products has been investigated in the last years. However limited information is available on wood characteristics and performance, mainly regarding chemical composition and durabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…Previous study was conducted on T. oak heartwood from different site in Kosovo, showing that the TPC ranged from 284.2 to 338.8 mg GAE/g extract by using ultrasonic bath at 40 °C and 50% ethanol/water solution as solvent (Bajraktari et al, 2018). This result is congruent with what we have reported here, and it confirmed that the solvent and the extraction technique substantially affect the content of secondary metabolites.…”
Section: Total Polyphenol (Tpc) and Flavonoid (Tfc) Content And Antio...supporting
confidence: 92%
See 1 more Smart Citation
“…Previous study was conducted on T. oak heartwood from different site in Kosovo, showing that the TPC ranged from 284.2 to 338.8 mg GAE/g extract by using ultrasonic bath at 40 °C and 50% ethanol/water solution as solvent (Bajraktari et al, 2018). This result is congruent with what we have reported here, and it confirmed that the solvent and the extraction technique substantially affect the content of secondary metabolites.…”
Section: Total Polyphenol (Tpc) and Flavonoid (Tfc) Content And Antio...supporting
confidence: 92%
“…This result is congruent with what we have reported here, and it confirmed that the solvent and the extraction technique substantially affect the content of secondary metabolites. Bajraktari et al, 2018 also investigated the presence of flavonoids in Q. cerris wood extract showing results as mg of catechin equivalent (mg CE) per gram of dry extract (range from 61.2 to 67.4 mg CE/g of dry extract).…”
Section: Total Polyphenol (Tpc) and Flavonoid (Tfc) Content And Antio...mentioning
confidence: 99%
“…Turkey oak coppice forests grow mainly in the Mediterranean area (Bajraktari et al, 2018;Picchio et al, 2009). In Italy, they extend for over 1,000,000 ha, representing 11.5% of the national woodland, 9.7% of the forest area and 3.4% of the land surface (IFNC, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In other recent study, the toxic effects of some Malaysian timbers heartwood extracts have been studied against some termite species and showed that high termite mortality was only achieved with Madhuca utilis extracts and methanol solvents (Kadir 2017). Bajraktari et al (2018) determined the extractive content of Turkey oak (Quercus cerris) and showed that comparatively low amount of phenolics and tannins in comparison with other oaks (Bajraktari et al 2018). The effectiveness of heartwood extracts of two Morus species against termites has been investigated and these substances have been found to be effective in preventing termite activity (Hassan et al 2019).…”
Section: Introductionmentioning
confidence: 99%